1995
DOI: 10.1046/j.1471-4159.1995.65062716.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor‐α and Basic Fibroblast Growth Factor Decrease Glial Fibrillary Acidic Protein and Its Encoding mRNA in Astrocyte Cultures and Glioblastoma Cells

Abstract: Tumor necrosis factor‐α is a pluripotent cytokine that is reportedly mitogenic to astrocytes. We examined expression of the astrocyte intermediate filament component glial fibrillary acidic protein in astrocyte cultures and the U373 glioblastoma cell line after treatment with tumor necrosis factor‐α. Treatment with tumor necrosis factor‐α for 72 h resulted in a decrease in content of glial fibrillary acidic protein and its encoding mRNA. At the same time, tumor necrosis factor‐α treatment increased the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In this context, it is interesting to note that decreased GFAP expression by astrocytes has previously been described in central pontine myelinolysis [8]. Furthermore, in vitro experiments have shown that GFAP is downregulated in astrocytes from mature brain in response to tumour necrosis factor‐α, and in fetal astrocytes, in response to IL‐1β[14,16,22]. Combined, these observations suggest that the reciprocal relationship in expression of peripherin and GFAP may be cytokine‐mediated.…”
Section: Discussionmentioning
confidence: 82%
“…In this context, it is interesting to note that decreased GFAP expression by astrocytes has previously been described in central pontine myelinolysis [8]. Furthermore, in vitro experiments have shown that GFAP is downregulated in astrocytes from mature brain in response to tumour necrosis factor‐α, and in fetal astrocytes, in response to IL‐1β[14,16,22]. Combined, these observations suggest that the reciprocal relationship in expression of peripherin and GFAP may be cytokine‐mediated.…”
Section: Discussionmentioning
confidence: 82%
“…We chose U373 cells as these are a well-characterized model of cultured glial cells that retain many of the responses of primary astrocytes (Murphy et al, 1995;Blom et al, 1997). A23187 treatment of U373 cells strongly induced binding of nuclear proteins to two different NFAT consensus sites, from the IL-2 and VIP promoters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the astroglial cell number and cell trophy (GFAP expression), it’s reported that activated microglia enhance the astrocyte growth but do not have a hypertrophic effect on astrocyte (Rohl et al , 2007). Besids, proinflammatory cytokines like IL-1 and TNFα are reported to produce a decrease of GFAP expression in astrocyte culture (Selmaj et al , 1991; Oh et al , 1993; Lee et al , 1995; Murphy et al , 1995). It’s speculated that activated microglia might be to a great extent involved in the onset of astrogliosis but other or additional cell interaction might be responsible for the typical increase of GFAP in astrogliosis.…”
Section: Discussionmentioning
confidence: 99%